“Empty spaces ‘Where’ we are living for” – First record of Dinoponera quadriceps reusing nests of Atta sexdens - Assis, Diego Santana; Morris, Sam; Nascimento, Fabio S (Sociobiology, 2017)
The reuse of nests by the same or different species can save a colony energy and resources. Furthermore, it can increase colony growth and the production of brood. The queenless ant Dinoponera quadriceps builds deep nests in Caatinga to escape from the dry and hot environment. The reuse of deep nests from other species can provide D. quadriceps with protection from high temperature, whilst saving on the energy required to build new nests. Here, we present the first finding of D. quadriceps reusing the nest of Atta sexdens species.